Relationship of symptom severity and bother in individuals seeking care for lower urinary tract symptoms. Issue 8 (6th August 2020) - Agochukwu‐Mmonu, Nnenaya; Wiseman, Jonathan B.; Smith, Abigail R.; Helmuth, Margaret E.; Sarma, Aruna V.; Cameron, Anne P.; Amundsen, Cindy L.; Flynn, Kathryn E.; Cella, David; Weinfurt, Kevin P.; Kirkali, Ziya; Clemens, J. Quentin
Abstract: Aims: Bother attributed to lower urinary tract symptoms (LUTS) drives care‐seeking and treatment aggressiveness. The longitudinal relationship of LUTS severity and bother in a care‐seeking cohort, however, is not well understood. We aim to conduct a longitudinal evaluation of LUTS severity and bother and identify characteristics of patients with discordant LUTS bother relative to severity. Methods: Men and women with LUTS seeking care at six US tertiary care centers enrolled in the symptoms of lower urinary tract dysfunction research network study. Patients reporting at least one urinary symptom based on the LUTS Tool were prospectively enrolled from June 2015 to January 2017. Correlations were used to assess the relationship between LUTS severity and bother. Discordance scores (ie, the difference between bother and severity) were used to classify patients with high and low bother. Patients were classified as having high or low bother phenotypes if scores were one standard deviation above or below zero, respectively. Repeated measures multinomial logistic regression evaluated characteristics associated with high and low bother phenotypes. Results: LUTS severity and bother were at least moderately correlated for all symptom items and highly correlated for 13 out of 21 items. Correlations were highest for urgency, and lowest for daytime frequency and urinary incontinence. Odds of being in high bother phenotype were lowest at 3 and 12 months (3 months vs baseline odds ratio [OR] = 0.71, 95% confidence ninterval [CI] = 0.54‐0.94; 12 months vs baseline OR = 0.66, 95% CI = 0.48‐0.91), and highest for those who endorsed all urgency questions (OR = 3.65, 95% CI = 2.17‐6.13). Odds of being in the low bother phenotype were lowest for patients who endorsed all urgency items (OR = 0.33, 95% CI = 0.26‐0.42), and all frequency items (OR = 0.68, 95% CI = 0.53‐0.88). Conclusions: LUTS severity and bother correlate highly and measurement of both in clinical practice is likely redundant. There are patient factors associated with discordance which may justify additional evaluation.